Perturbed T cell IL7 receptor-signaling in chronic Chagas disease - Albareda, M. Cecilia (J Immunol, 2015)
We have previously demonstrated that immune responses in subjects with chronic Trypanosoma cruzi infection display features common to other persistent infections with signs of T cell exhaustion. Alterations in cytokine receptor signal transduction have emerged as one of the cell-intrinsic mechanisms of T cell exhaustion. Herein, we performed an analysis of the expression of IL-7R components (CD127 and CD132) on CD4(+) and CD8(+) T cells, and evaluated IL-7-dependent signaling events in patients at different clinical stages of chronic chagasic heart disease. Subjects with no signs of cardiac disease showed a decrease in CD127(+)CD132(+) cells and a reciprocal gain of CD127(-)CD132(+) in CD8(+) and CD4(+) T cells compared to either patients exhibiting heart enlargement or uninfected controls. T. cruzi infection, in vitro, was able to stimulate the downregulation of CD127 and the upregulation of CD132 on T cells. IL-7-induced phosphorylation of STAT5 as well as Bcl-2 and CD25 expression were lower in T. cruzi-infected subjects compared with uninfected controls. The serum levels of IL-7 was also increased in chronic chagasic patients. The present study highlights perturbed IL-7/IL-7R T cell signaling through STAT5 as a potential mechanism of T cell exhaustion in chronic T. cruzi infection.